Tourist Activity of Women Living in Polish Rural Areas - Jerzy Eider; Elżbieta Sieńko-Awierianów (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Tourism, especially adventure tourism, is the best form of physical activity, regardless of age, gender and wealth. It is one of the most important and most accessible forms of active recreation. Although socio-economic transformation in the early 1990s had a profound influence on the development of tourism in Poland, for some social groups tourism is still a luxury. The situation of rural women in this regard is particularly difficult. The aim of this study was to evaluate the tourist activity of rural women and find out its main determinants. To achieve these objectives, a survey was conducted among women living in the villages of Koszewo, Pęzino and Kunowo (district of Stargard Szczeciński, West Pomerania). The study showed the increased level of education of rural women and their improved standards of living, clearly reflected in the increased awareness of healthy leisure activities. Analysis of ways of spending vacations by women living in rural areas showed that it depended on their economic activity but not on education. Going abroad for vacations and frequency of trips outside the place of residence depended on both education and economic activity of the surveyed women.